Anthropogenic Pressures on Grey Junglefowl (Gallus sonneratii) Habitats at Gudalur Range in Theni forest Division, Western Ghats, Tamil Nadu - Ramesh, N.; Sathyanarayana, M. C. (Indian Forester, 2009)
894 cattle and 250 goats visited Gudalur Range from three villages/settlements. A total of 37 food plant species of Grey Junglefowl were recorded. Out of 37 plant species observed, 15% of the plant species have been trampled by the scrub cattle. The cattle browsed 50% of plant species and grazed 5% of plant species. Forty five firewood collectors visited the forest area to collect 1,125 kgs of fire wood. Out of 15 plant species, Schleichera oleosa, Grewia tillifolia and Acacia torta were the dominant plant species preferred as firewood by the local people. They carried the fire wood by head load (n=41), by cycle (n=3) and by motor cycle (n=1). They sold the fire wood for Rs. 60-75 per load to the local tea shop. It was observed 60% of the fire wood for sale and 40% for own use. At Gudalur range 12 Non Timber Forest Produce (NTFP) items were collected by 760 local people throughout the year. Disturbances associated with two hydroelectric projects are also having a negative influence in the area. Three metal roads criss cross the study area where the wild animals were accidentally killed by the vehicles. There are two temples located in the boundary of the reserve forest where the pilgrims visited often. Mangala Devi Kannaki temple is situated in the hill top (1,050 m) of the study area where many thousands of people visit every year to worship the Goddess Kannaki. There is an urgent need for surveys to be done to determine the whereabouts of viable populations of the Grey junglefowl. It is essential as a long-term aim that conservation education should encourage people as the Grey Junglefowl is involved in seed dispersal, controlling insect pest in the forest level and fall prey on predators ; totally it is maintaining the ecosystem in the wild.